GENERAL GEOLOGY AND ENGINEERING GEOLOGY AT KM40-KM30 LOJING-GUA MUSANG ROAD, KELANTAN - MOHD AZAM, MOHD AMIRUL NASRIN (2016)
Slope stability has become an important issue in the engineering geology as it affects the safety of the surrounding environment as the study example is a slope at the major road. Failure of slopes are generally caused by the conditions of the rocks and also the external factors which enhance the failure potential. The condition of rocks is altered due to chemical and sometimes by the physical weathering. Due to these factors, it causes the rock to become weak and less cohesive thus results in the formation of joints and fractures. This study provided an input for engineering geology at KM40-KM30 Lojing-Gua Musang road which has the potential to become a geohazard and the ways to prevent it. To achieve ultimate objectives; petrographic analysis, stereonet analysis, geological mapping and rock mass classification are the methods used. For limestone rock, the estimated Uniaxial Compressive Strength (UCS) is 73 MPa based on 20 samples has taken. There are three fracture sets within the rock mass. The discontinuity spacing is moderate spacing based on the classification that recommend by ISRM. The Rock Quality Designation (RQD) for this rock is 99%. The condition of discontinuities is about rough, unweathered and no infilling. For the overall of rock mass basic rating, the value is 82 which means very good rock.